EU-ASEAN: Shared objectives, severed trust - Hosuk Lee-Makiyama; Joses Wong (European Centre for International Political Economy (ECIPE), 2023)
After 45 years of diplomatic dialogue, EU-ASEAN relations continue to dawdle, lacking real ambition or political will from either side to invest more in the relationship. Even after a recent upgrade in the relationship to a strategic partnership (and continued pressure from the business communities on both sides to do more), the potential of the EU-ASEAN relationship is still not well understood by policymakers.
Keywords: 330